2017
DOI: 10.4236/adr.2017.53013
|View full text |Cite
|
Sign up to set email alerts
|

Design of Interactive Tutorials on Mobile Applications for Chinese Middle-Aged and Older Adults

Abstract: With the rapid speed of development for information technology in China, Chinese middle-aged and older adults benefit from various of mobile applications and services. However, most of them have difficulty to learn to use these mobile technologies. Thus, the goal of research is to design an interactive tutorial for middle-aged and older adults, which can adapt to existing applications. By conducting a survey to investigate their requirements for smartphone mobile applications tutorials and doing empirical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Learners were very pleased with the way the videos were produced and the features they offered, namely narration and subtitles, and the fact that they were on YouTube, which made them available at any time. These results are consistent with the findings of and Chen et al (2017), who concluded that videos should contain multiple pieces of information. These studies have also found that the duration of video lessons plays a very important role, as they can be tedious if they are too long.…”
Section: Findings and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Learners were very pleased with the way the videos were produced and the features they offered, namely narration and subtitles, and the fact that they were on YouTube, which made them available at any time. These results are consistent with the findings of and Chen et al (2017), who concluded that videos should contain multiple pieces of information. These studies have also found that the duration of video lessons plays a very important role, as they can be tedious if they are too long.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…This piece of information can be used when designing lessons on the use of smartphones for older people. In a similar vein, the findings of this study showed that, due to the ease of access via YouTube and the embedded narration and subtitles, video lessons might prove to be useful in a blended learning programme as they help participants learn easier and faster Chen et al, 2017). Women's views on the effectiveness of video lessons compared to face-to-face lessons tend to be similar, "I believe that they are almost on par with face-to-face lessons"(L4), and they also seemed to appreciate the flexibility in terms of time and location that they offer, "I watched most videos twice, but the best thing was that they were all on YouTube, which meant I could watch them whenever and wherever I wanted" (L3).…”
Section: Findings and Discussionsupporting
confidence: 56%
See 1 more Smart Citation